Advance care planning within survivorship care plans for older cancer survivors: A systematic review. (November 2017) - O'Caoimh, Rónán; Cornally, Nicola; O'Sullivan, Ronan; Hally, Ruth; Weathers, Elizabeth; Lavan, Amanda H.; Kearns, Tara; Coffey, Alice; McGlade, Ciara; Molloy, D. William
Graphical abstract: Advance care planning within survivorship care plans for older cancer survivors: a systematic review. Highlights: We reviewed the evidence for advance care planning, including advance care directives in survivorship care plans, among older cancer survivors. No papers were found that met inclusion criteria, with only one survivorship care plan including mention of an advance care directive. Despite increasing numbers of older and frail cancer survivors, there is little evidence for the use of advance care planning after cancer. Future studies should establish their acceptability and utility among older cancer survivors. Abstract: Advances in the medical treatment of cancer have increased the number of survivors, particularly among older adults, who now represent the majority of these. Survivorship care plans (SCPs) are documents that cancer patients receive summarising their care, usually at the end of treatment but preferably from initial diagnosis. These may increase patient satisfaction and represent an opportunity to initiate preventative strategies and address future care needs. Advance care planning (ACP), incorporating advance healthcare decision-making, including formal written directives, increases satisfaction and end-of-life care. This paper systematically reviews evaluations of ACP within SCPs among older (≥65 years) cancer survivors. No studies meeting the inclusion criteria were identified by search strategies conducted in PubMed/MEDLINE and the Cochrane databases. One paper examined cancer survivors' mainly positive views of ACP. Another discussed the use of a SCP supported by a 'distress inventory' that included an advance care directive (living will) as an issue, though no formal evaluation was reported. Although ACP is important for older adults, no study was found that evaluated its role within survivorship care planning. Despite the risk of recurrence and the potential for morbidity and mortality, especially among older cancer survivors, ACP is not yet a feature of SCPs.